2018
DOI: 10.1002/lary.27206
|View full text |Cite
|
Sign up to set email alerts
|

Malleostapedotomy in stapes revision surgery: Is an endoscopic approach possible?

Abstract: 4. Laryngoscope, 2611-2614, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…A close analysis of the incus and accurate evaluation of the extent of necrosis requires excellent visualization of the ossicular chain. Similarly, malleostapedotomy requires detailed visualization and inspection of the oval window and lateral ossicular chain; the endoscopic approach has been applied in this setting and shown to be effective in a small case series . Notably, the cause of surgical failure was accurately diagnosed with imaging in one of three patients who had preoperative CT scans; however, conclusions regarding the utility of preoperative CT scans cannot be drawn from this small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…A close analysis of the incus and accurate evaluation of the extent of necrosis requires excellent visualization of the ossicular chain. Similarly, malleostapedotomy requires detailed visualization and inspection of the oval window and lateral ossicular chain; the endoscopic approach has been applied in this setting and shown to be effective in a small case series . Notably, the cause of surgical failure was accurately diagnosed with imaging in one of three patients who had preoperative CT scans; however, conclusions regarding the utility of preoperative CT scans cannot be drawn from this small sample size.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 , 7 However, current research on endoscopic stapes surgery is limited to traditional incudostapedotomy despite the fact that malleostapedotomy can be performed entirely using an endoscope alone, as demonstrated by Iannella et al in six revision stapes surgery cases. 8 To date, this is the only clinical study on endoscopic malleostapedotomy (EMS). Moreover, no studies have compared the surgical outcomes of EMS and endoscopic incudostapedotomy (EIS).…”
Section: Introductionmentioning
confidence: 99%
“…M alleostapedotomy (MS), also known as malleovestibulopexy or malleus grip stapedotomy, is an otologic procedure in which the prosthesis is attached to the malleus on one end and the stapes footplate on the other end. This procedure was first introduced by Fisch et al 1,2 Malleostapedotomy is performed mainly in revision cases where the lateral ossicular chain is fixed, for management of advanced tympanosclerosis involving the oval window and for cases of eroded incus. 1,2 Like any other surgery, MS has its own challenges including selection of the appropriate prosthesis which will have a significant impact on MS success.…”
mentioning
confidence: 99%
“…This procedure was first introduced by Fisch et al 1,2 Malleostapedotomy is performed mainly in revision cases where the lateral ossicular chain is fixed, for management of advanced tympanosclerosis involving the oval window and for cases of eroded incus. 1,2 Like any other surgery, MS has its own challenges including selection of the appropriate prosthesis which will have a significant impact on MS success. In a temporal bone dissection study, they have found that the average distance should be 6.3 mm between the site of MS crimp and stapedotomy site (range: 5.75-7.0 mm).…”
mentioning
confidence: 99%
See 1 more Smart Citation